An NMR microscopy study of water absorption in cork (Journal of Materials Science, 2000)
NMR Microscopy is used to measure the imbibition of water into natural cork, extractives-free cork and desuberised cork. The results clearly indicate that suberin is the key constituent which determines the ability of cork to resist water uptake. Furthermore, a particular suberin with distinct spectral properties as viewed by 13C NMR is shown to be the component responsible for cork resistance to water absorption. Laser confocal microscopy suggests that this function is associated with the role of suberin in preserving cell wall structure but the highly hydrophobic nature of suberin may also play an important role. The NMR microscopy study shows that the water absorbed by natural cork, after soaking for three days, is confined to the lenticels, narrow channels on the order of 1000 to 1500 μm in diameter. One incidental outcome is the observation of a clear down-field shift in NMR frequency for water near the cut transverse surfaces of the cork, an effect~associated with susceptibility inhomogeneity.